Is a Uniform Price on Carbon Desirable? A Public Finance Perspective - Felix Bierbrauer (CESifo GmbH, 2024)
Should climate policy rely on a price of Carbon that is uniform across sectors? This paper studies this question from a public finance perspective. It is found that a justification for a uniform price can be given, but it relies on strong assumptions, among them indifference with respect to the distributive consequences of climate policy. Distributive considerations may imply that sectors whose output is consumed mostly by “the poor” should contribute less to meeting the government's emission target, whereas sectors whose output is consumed mostly by “the rich” should contribute more.
Keywords: D63; H21; H22; Q58; 330; climate policy; equity-efficiency trade-off; optimal taxation